MANTLE CELL LYMPHOMA – A REVIEW OF RESEARCH - Hanna Pietruszewska; Katarzyna Kleszczewska; Agnieszka Pruska; Natalia Senatorska; Julia Rarok; Daria Godlewska; Monika Banaszek; Agata Panfil; Julia Błocka; Agata Lurka (International Journal of Innovative Technologies in Social Science, 2025)
Mantle cell lymphoma remains a cancer with a high risk of recurrence, but advances in treatment are significantly changing the prognosis for patients. Molecularly targeted therapies, such as the combination of ibrutinib and venetoclax, as well as immunotherapy using CAR-T cells (chimeric antigen receptor T-cells), show high clinical efficacy and the potential for sustained remission. Research results indicate a significant prolongation of progression-free survival with an acceptable safety profile. Further development of therapeutic strategies should focus on personalising treatment, identifying response biomarkers and minimising adverse effects. These advances offer a real chance for long-term disease control. The aim of this study is to evaluate the efficacy and safety of modern molecularly targeted and cellular therapies in the treatment of mantle cell lymphoma, with particular emphasis on their impact on remission duration, progression-free survival and the possibility of long-term disease control. The study aims to highlight the importance of individualising treatment, integrating different therapeutic methods and identifying biomarkers that can support a more precise clinical approach.